The effect of visual distractions on speech perception in children. - Keetay V (Volta Review)
Anecdotal parental reports have raised concerns that visual distractions in general education classrooms may negatively affect hearing-impaired children's speech perception. The literature supports this potential problem, which could have educational implications for inclusion. To investigate, this study compared continuous discourse tracking rates in 16 children (8 with hearing impairments and 8 with normal hearing) using three competing noise conditions: classroom noise, videotaped classroom activity, and combined noise and visual activity. The design used multiple baselines across subjects followed by alternating treatments. Statistical analyses showed no significant differences among tracking rates due to the distractors. The results suggest that children with hearing impairments may not necessarily be at risk for reduced speech perception due to visually busy classrooms, which has positive implications for inclusion.